O uso do STarT (Subgroups Target Treatment) back screening tool no Brasil - Medeiros, Flávia Cordeiro de (2019)
Background: Low back pain causes a high socioeconomic impact in the world population. In order to identify the prognosis for low back pain, nine items of unfavorable prognostic factors were grouped in an instrument named STarT Back Screening Tool (SBST). The SBST, which is the main topic of this thesis, allows to classify patients with low back pain into low, medium or high-risk of a poor prognosis. SBST has been used in several countries and at different levels of health care. To date, the literature on the application of the SBST in developing countries is still scarce. Therefore, the general objective was to explore the application of the SBST in a sample of the Brazilian population. Methods and results: This thesis was composed of nine chapters, being five chapters corresponding to prospective cohort studies investigating the use of the SBST in Brazil. Two chapters (Chapter 2 and Chapter 3) involved 148 patients with chronic low back pain from the physical therapy department. Two other chapters (Chapter 4 and Chapter 6) involved 200 patients with acute low back pain from emergency department. One chapter (Chapter 5) involved 348 patients from the previous samples mentioned above. The main results of these studies were: 1) The SBST was able to stratify clinical characteristics among the different subgroups, including disability, intensity of pain, anxiety and depression (chapters 2, 3, 4, 5 and 6); 2) Patients classified as high-risk always present more intense symptoms, compared to the other subgroups (chapters 2, 3, 4, 5 and 6); 3) The SBST presented better performance to predict long term disability when compared to prediction of pain intensity (chapters 2, 3 and 4); 4) The SBST was not able to predict recurrence of an episode of acute low back pain in one year (Chapter 6); 5) Most of patients with low back pain changed subgroup after six weeks when receiving emergency care or physical therapy (Chapter 3 and 4); 6) The best time to use the SBST to stratify characteristics xxxi and predict outcomes is after six weeks in both acute and chronic low back pain patients. This is due to the fact that SBST was not able to predict clinical outcomes when applied at baseline and adjusted for possible confounders (Chapters 3 and 4); 7) The SBST is able to detect short- and medium-term clinical change in patients with acute or chronic low back pain and seems to perform better in patients with acute low back pain (Chapter 5). In addition to the chapters already presented, this thesis is composed of two more chapters that are not specific about the use of the SBST in Brazil, however, address related topics. One of the chapters (Chapter 7) describes a retrospective epidemiological study involving 37,080 patients to investigate the characteristics and approach of patients with spinal pain in a private emergency department. In this study, it was identified that spinal pain is a common health condition in the emergency department, accounting for about 20% of all visits related to orthopedics between 2011 and 2017. It was also observed that the amount of imaging exam and medications prescribed for these patients is excessive compared to the recommendations of the guidelines of clinical practice. In the last chapter (Chapter 8), the objectives were to translate and cross-culturally adapt the Keele STarT MSK Tool to the Brazilian Portuguese and to test the measurement properties of this instrument. A total of the 151 patients with neck, low back, shoulder and knee pain were assessed. The internal consistency presented values lower than accepted benchmark in the Brazilian population. However, the reliability, agreement, construct validity and ceiling and floor effect tests were considered acceptable when compared to the original version.